1984
DOI: 10.1161/01.cir.69.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in regional myocardial metabolism, perfusion, and wall motion in Duchenne muscular dystrophy studied by radionuclide imaging.

Abstract: Studies at necropsy have shown that the cardiomyopathy of Duchenne muscular dystrophy selects the posterobasal and contiguous lateral left ventricular (LV) walls as initial and primary sites of myocardial dystrophy in the absence of small-vessel coronary artery disease in these areas. The present investigation was designed chiefly to determine whether a myocardial metabolic abnormality could be identified in these same areas during a patient's life. Positron emission computed tomography was used to study regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(48 citation statements)
references
References 53 publications
4
41
1
2
Order By: Relevance
“…Three of 4 regions manifested significantly decreased circumferential strain, as did the basal and midventricular segments by repeated-measures ANOVA. In contrast to the present findings, previous investigations with standard echocardiography and radionuclide imaging have reported the primary defects of cardiac involvement in DMD to reside within the inferior 20,21 or posterolateral walls. 22 The reason for this difference most probably reflects the enhanced sensitivity of CMR for detecting widespread but subtle changes of intramural contractile function, which are interpretable only at regional or global levels with the use of alternative technologies.…”
Section: Discussioncontrasting
confidence: 99%
“…Three of 4 regions manifested significantly decreased circumferential strain, as did the basal and midventricular segments by repeated-measures ANOVA. In contrast to the present findings, previous investigations with standard echocardiography and radionuclide imaging have reported the primary defects of cardiac involvement in DMD to reside within the inferior 20,21 or posterolateral walls. 22 The reason for this difference most probably reflects the enhanced sensitivity of CMR for detecting widespread but subtle changes of intramural contractile function, which are interpretable only at regional or global levels with the use of alternative technologies.…”
Section: Discussioncontrasting
confidence: 99%
“…Yamamoto et al reported that hypoperfusion or perfusion defects are frequently observed in the posterior and apical walls, 18 and Perloff et al reported that 201 Tl-SPECT and 18 F-fluorodeoxyglucose positron emission tomography can reveal hypoperfusion or perfusion defects in the posterolateral wall. 19 Our results agree with these previous reports. We also found that, in areas with hypoperfusion or perfusion defects, the degree of myocardial fibrosis and fatty infiltration was more severe and extended transmurally.…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported that 201 Tl-SPECT perfusion defects are frequently seen in the posterolateral wall of the left ventricle in patients with DMD, [18][19][20] and we have also observed the redistribution phenomenon on delayed resting 201 Tl-SPECT images in some patients with DMD. Although the redistribution phenomenon is seen in patients with coronary artery disease, 21 no previous reports have described such a phenomenon or its pathophysiologic correlation in patients with DMD.…”
supporting
confidence: 76%
“…Right or left bundle branch block, left ventricular hypertrophy 28 Acute myocardial ischemia or infarction 29 Acute myocarditis 30 Right ventricular ischemia or infarction 31 Dissecting aortic aneurysm 32 Acute pulmonary thromboemboli 33 Various central and autonomic nervous system abnormalities 34,35 Heterocyclic antidepressant overdose 36 Duchenne muscular dystrophy 37 Friedreich's ataxia 38 Thiamine deficiency 39,40 Hypercalcemia 41 Hyperkalemia 42 Cocaine intoxication 43,44 Mediastinal tumor compressing RVOT 45 Arrhythmogenic right ventricular dysplasia/cardiomyopathy 24,25 Long-QT syndrome, type 3 11,12 Other conditions that can lead to ST-segment elevation in the right precordial leads…”
Section: Table 2 Abnormalities That Can Lead To St-segment Elevationmentioning
confidence: 99%